Strides Toward Recovery From Intimate Partner Violence: Elucidating Patient-Centered Outcomes to Optimize a Brief Counseling Intervention for Women - Grillo, Alessandra R. (Journal of interpersonal violence, 2021)
Women in the United States continue to experience intimate partner violence (IPV) at unprecedented rates, necessitating the development and implementation of personalized, effective healthcare-based interventions. Methods of developing patient-centered interventions for IPV should elicit the voice of the target population (i.e., women who experience IPV) while assuring that outcomes identified as important are incorporated into the refined intervention. This pilot study is part of a multiphase, larger study aiming to refine an IPV intervention and clinical outcome measurements prior to formal evaluation of the effectiveness of the intervention. Specifically, this study elucidates patient-centered outcomes identified by women who have experienced IPV. Women patients of the Veterans Health Administration (VHA) in New England participated in focus groups to provide feedback and desired outcomes of a new IPV intervention. Patient-centered outcomes were defined by the participants. Focus groups were transcribed and analyzed using conventional content analysis and matrix analysis. A total of 25 women participated in focus groups (n = 5) at two large VHA facilities. Participant feedback revealed five common themes related to desired outcomes. Women opined increased feelings of empowerment as a key outcome of engaging in an IPV intervention. Women desired increased social connectedness and support to be gained during treatment, citing providers and other survivors of IPV as exemplary sources. Self-esteem was viewed as critical to enhancing recovery, as was increased knowledge across domains of IPV (e.g., warning signs, the link between mental and physical health for self and children). Finally, women identified valued action and goal setting, such as achieving more independence, as an optimal outcome. Addressing IPV against women requires patient-centered interventions that specifically target the types of outcomes deemed important by the end users: women who experience IPV. Findings have implications for tailoring treatments for IPV and selecting measures that tap into women’s desired outcomes.